WUJUDKAN GURU SEKOLAH DASAR PROFESIONAL DI ERA DIGITAL - Rahmi Hanifah; Darmansyah; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The existence of technology becomes an influential part, especially in the world of education. For a teacher this condition is certainly a challenge, those who can keep up with developments will be replaced by technology. This phenomenon can be a threat to the teacher's existence, if the teacher is still struggling and only focuses on teaching with conventional learning methods. However, this does not mean it becomes a barrier for teachers to continue to spread knowledge. Conversely, teachers must have a high enthusiasm to adapt and improve their quality in teaching. An ideal teacher must understand how to become a teacher in the digital era. Moreover, being a teacher in an elementary school, students with an age range of around 6-12 years, if learning is presented using the lecture method, just reading textbooks, students will quickly feel bored with learning. For this reason, teachers are needed who are active, creative and careful in presenting digital learning in accordance with the demands of today's times, so that learning objectives will be more easily achieved. By referring to various authoritative literature in sufficient quantities, and presented in an analytical descriptive manner, this paper further focuses its discussion on the requirements of professional teachers needed in the digital era.